The influence mechanism of planned behavior and self-consciousness on learners’ willingness to use language learning Apps: Validation based on structural equation modeling - Yanyan Ren; Xiaoyong Tan (PLoS ONE, 2025)
The continuous development of digital technology facilitates the informatization of foreign language learning, making it possible to create a deeply integrated mobile learning environment which is conducive to enhancing learning efficiency. To investigate learners’ willingness to use mobile language leaning applications (Apps), this research is carried out under an extended theoretical framework of Technology Acceptance Model (TAM) and Theory of Planned Behavior (TAM) by incorporating self-consciousness. On the basis of the survey data of 728 college students, structural equation modeling is constructed and empirically tested with AMOS 23.0. Results show that the structural equation modeling based on the extended TAM-TPB framework is suitable for analyzing the influencing mechanism of learners’ willingness to use language learning Apps. College students’ willingness to use language learning Apps is directly affected by behavioral attitudes, subjective norms, and perceived behavior control. Perceived ease of use has a significant direct impact on perceived usefulness. However, perceived ease of use and perceived usefulness have different mediating effects on learners’ willingness to use language learning Apps through behavioral attitudes, subjective norms, and perceived behavior control. Based on the findings, this paper suggests that when developing language learning Apps, emphasis should be laid on the positive feedback of learners’ self-consciousness and user enjoyment, as well as the construction of a curriculum system centered on core competencies so as to enhance learners’ willingness to use language learning Apps, thereby promoting language learning efficiency.